Design and Evaluation of a Ship Fin Stabilizer System Based on Mamdani and Sugeno Fuzzy Logic Using MATLAB - Muhhammad Iyan Putra Pratama; Achmad Zain Nur; Dian Neipa Purnamasari (Sains Data Jurnal Studi Matematika dan Teknologi, 2025)
This study addresses the design and evaluation of a ship fin stabilizer control system aimed at damping roll and pitch motions caused by wave-induced disturbances. The system employs an MPU6050 sensor to acquire ship inclination angle data, which are subsequently processed by a fuzzy logic–based controller. Two fuzzy inference methods, namely Mamdani and Sugeno, are implemented and analyzed using MATLAB as the simulation platform. The input variables consist of roll and pitch angles, while the output variables correspond to the actuation angles of the right and left fin stabilizers. The system is designed with three membership functions for each input variable and a total of nine fuzzy rules. Simulation results demonstrate that the fuzzy controller is capable of generating adaptive fin angle responses that appropriately correspond to variations in ship inclination and maintain a stable condition under equilibrium states. The findings indicate that fuzzy logic offers a flexible and effective approach for ship stabilization systems in simulation-based environments.